Experimental investigation of a novel vertical loop-heat-pipe PV/T heat and power system under different height differences. (1st September 2022) - Yu, Min; Chen, Fucheng; Zhou, Jinzhi; Yuan, Yanping; Fan, Yi; Li, Guiqiang; Zhao, Xudong; Wang, Zhangyuan; Li, Jing; Zheng, Siming
Abstract : For a novel vertical solar loop-heat-pipe photovoltaic/thermal system, the height difference between evaporator and condenser plays an important role in the heat transport capacity, which has significant impact on the solar thermal efficiency and parametrical optimization of this system. Therefore, based on the results derived from the authors' previous analytical investigation and computer modelling studies, a prototype of this novel system was designed, constructed, and an experimental investigation under different height difference was undertaken to study the impact of height difference on the system performance. It was found that the relationship between the solar thermal efficiency of this vertical system and the height difference is nonlinear. In present study, the optimal height difference is around 1.1 m, which was selected as an optimal value for the following experimental investigations, and below 1.1 m, the PV module surface temperature decreased with the increase of the height difference. Furthermore, the transient solar thermal and electrical performance of this system with the selected optimal height difference were investigated under outdoor real weather condition. These results of this experimentation can help optimize the system construction and thus help to develop the high thermal performance and low-cost solar PV/T system for space heating and power generation. Highlights: A novel LHP-PV/T heat & power system was experimentally investigated by varying HD. The optimal height difference between evaporator and condenser is around 1.1 m. New PV/T system achieved higher solar efficiency compared to most existing ones. A lower inlet water temperature led to the increased solar thermal efficiency.